Changes of characteristics of daily precipitation and runoff in the High Tatra Mountains, Slovakia over the last fifty years - BIČÁROVÁ, Svetlana; HOLKO, Ladislav (Contributions to Geophysics and Geodesy, 2013)
The article presents the results of the analysis of time series of daily precipitation and runoff at selected places in the highest part of the Western Carpathians. It was focused on both wet and dry periods in precipitation and runoff data series. The precipitation data were analysed for a period 1961–2010. They revealed a significant increase of the number of days with daily precipitation 40–60 mm. Trend analysis for 67 analysed flow characteristics did not show statistically significant changes over the studied period. The focus was given particularly to the characteristics of the maximum and minimum flows, i.e. 3- and 7- day minimum flows, 1-, 3- and 7-day maximum flows. We found an increase of flows classified as small floods in two of three mountain catchments in the study area in the last decade (2001–2010). It may be linked to the above increased number of days with daily precipitation reaching 40–60 mm.